Transcatheter Atrial Septal Defect Closure in Children with and without Fluoroscopy: A Comparison. (7th April 2019) - Ackermann, S.; Quandt, D.; Hagenbuch, N.; Niesse, O.; Christmann, M.; Knirsch, W.; Kretschmar, O.
Abstract : Objective . The aim of this study was to compare feasibility, effectiveness, safety, and outcome of atrial septal defect (ASD) device closure in children with and without fluoroscopy guidance. Methods and Results . Children undergoing transcatheter ASD closure between 2002 and 2016 were included into this single center, retrospective study. Patients were analysed in two groups [1: intraprocedural fluoroscopy ± transoesophageal echocardiography (TOE) guidance; 2: TOE guidance alone]. Three-hundred-ninety-seven children were included, 238 (97 male) in group 1 and 159 (56 male) in group 2. Two-hundred-twenty-nine of 238 (96%) patients underwent successful fluoroscopy guided ASD closures versus 154/159 (97%) successful procedures with TOE guidance alone. Median weight (IQR) at intervention was 20kg (16.0-35.0) in group 1 versus 19.3kg (16.0-31.2) in group 2. Mean (SD) preinterventional ASD diameter was 12.4mm (4.4) in group 1 versus 12.2mm (3.9) in group 2. There was no significant difference in number of defects or characteristics of ASD rims. Median procedure time was shorter in group 2 [60min (47-86) versus 34min (28-44)]. Device-size-to-defect-ratio was similar in both groups [group 1: 1.07 versus group 2: 1.09]. There were less technical intraprocedural events in group 2 [10 (6.3%) versus 47 (20%)]. Intraprocedural complications were less frequent in group 2 [1 (0.6%) versus 8 (3.3%)]. Conclusion . Transcatheter ASD device closure with TOE guidance alone (i.e., without fluoroscopy) is as effective and safe as ASD closure with fluoroscopy guidance. As fluoroscopy remains an important adjunct to transoesophageal echocardiography, especially in complex defects and complications, procedures are always performed in a fully equipped cardiac catheterization laboratory.